An analysis of the 2013 National Budget Statement and its implications for social work practise in Zimbabwe - Mtetwa, Edmos; Muridzo, Noel G. (2020)
This paper reviews the 2013 National Budget for Zimbabwe that was presented in Parliament on 15 November 2012. The authors interrogate the extent to which the budget as a policy instrument fosters the developmental agenda. Selected key areas of human development are reviewed. Although estimates of expenditure are a reflection of the national economic policy direction, the current paper shall dwell much on the policy prescription of the budget in the light of scarce resources available in an economy still recovering from a decade of recession.